Direct Bacterial Count as a Rapid Freshness Test for Fish Fillets - Lerke, Peter (1969)
Comparison of various indices of deterioration of refrigerated fish fillets showed that the direct bacterial count can be used to predict the storage life of the foodstuff. For direct counts, a thin film made from fillet surface material was spread on a microscope slide, stained, and read. Initial counts were found to correlate well with keeping quality; a period of freshness of 24 or 48 hr at 5 C could be reliably predicted. Preliminary data indicated that hypoxanthine estimation could probably also be used for the prediction of shelf life but that the relative complexity of the procedure detracted from its usefulness.